The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1136/bmjopen-2018-021670
|View full text |Cite
|
Sign up to set email alerts
|

In which groups of pregnant women can the caesarean delivery rate likely be reduced safely in the USA? A multicentre cross-sectional study

Abstract: ObjectivesTo identify obstetrical subgroups in which (1) the caesarean delivery (CD) rate may be reduced without compromising safety and (2) CD may be associated with better perinatal outcomes.DesignA multicentre cross-sectional study.Setting19 hospitals in the USA that participated in the Consortium on Safe Labor.Participants228 562 pregnant women in 2002–2008.Main outcome measuresMaternal and neonatal safety was measured using the individual Weighted Adverse Outcome Score.MethodsWomen were divided into 10 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
11
1
1
Order By: Relevance
“…Using our multivariable model, we were essentially able to compare outcomes from all hospitals after implementation of the program to their own pre-implementation outcomes as well as to the outcomes from other hospitals who had not yet implemented the program at the same calendar time. As well, the use of previously developed and used [5, 6, 1820] indicators for adverse maternal and neonatal outcomes, the mAOI and WAOS, further strengthens our results. Given the multifaceted nature of the MORE OB program, we considered that indicators capturing multiple components of maternal/newborn care would be more appropriate.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Using our multivariable model, we were essentially able to compare outcomes from all hospitals after implementation of the program to their own pre-implementation outcomes as well as to the outcomes from other hospitals who had not yet implemented the program at the same calendar time. As well, the use of previously developed and used [5, 6, 1820] indicators for adverse maternal and neonatal outcomes, the mAOI and WAOS, further strengthens our results. Given the multifaceted nature of the MORE OB program, we considered that indicators capturing multiple components of maternal/newborn care would be more appropriate.…”
Section: Discussionsupporting
confidence: 84%
“…The decision to use these two composite indices was made for several reasons. Using previously-developed measures facilitates comparison between our study and previously published research [5, 6, 1820]. Further, the MORE OB program is comprehensive and multifaceted, and could affect a number of maternal and newborn outcomes.…”
Section: Methodsmentioning
confidence: 79%
“…This situation is suggestive of a vicious cycle in which nulliparous women receive care that does not allow them to go into labor spontaneously and are subjected to interventions that result in high cesarean section rates in group 1, which was 39.0%, contrasting studies from other countries, such as the Netherlands, where group 1 showed a cesarean section rate of 9.6%13, and in the United States, where this rate was 14.8%. 16 In this study, cesarean section rates in nulliparous women with a single pregnancy and fetus in cephalic presentation (groups 1 and 2) was 49.3%, which was higher than the Lucena FS et al 17 found a cesarean section rate of 35.8% in nulliparous women with a single pregnancy and fetus in cephalic presentation assisted in the Brazilian public health services. Noteworthy is that group 2 (nulliparous women who did not go into labor spontaneously) were the second-largest relative contribution in the global cesarean section rate with 21.5% in São Paulo State, reaching 27.3% in public hospitals in the low urbanized region.…”
Section: Discussioncontrasting
confidence: 53%
“…Ideally, the induced labour progresses to a vaginal birth. However, despite randomised controlled trials indicating that IOL does not increase caesarean section rates3 4 outside of the tight confines of trials, the reality for women in high-income nations is that up to ~40% of women having their labours induced will require a caesarean section, this is particularly true if they are nulliparous 5–9…”
Section: Introductionmentioning
confidence: 99%